Dermoscopy of cutaneous adnexal tumours: a systematic review of the literature. (25th May 2022) - Lai, M.; Muscianese, M.; Piana, S.; Chester, J.; Borsari, S.; Paolino, G.; Pellacani, G.; Longo, C.; Pampena, R.
Abstract: Cutaneous adnexal tumours (ATs) encompass a variegated group of hamartomas and benign or malignant tumours, originating from the hair follicle, sebaceous, eccrine or apocrine glands that may simulate other cutaneous neoplasms. This study aims to provide a comprehensive overview of the spectrum of clinical and dermoscopic features of ATs, to better define these lesions and assist in the differential diagnosis. We performed a two‐step systematic search of the literature in PubMed, Embase and Cochrane Library databases from inception until 4 September 2020. In the first step, we aimed to define histological variants of ATs with descriptions of dermoscopic criteria. The second step included a search for the name of each previously identified AT variants in the same databases adding 'AND (epilum* or dermosc* or dermatosc*)'. All study types in English language reporting dermoscopic images of ATs were included. Collisions between ATs and other inflammatory or neoplastic skin lesions were excluded, with the exception of collisions with a sebaceous nevus. The protocol of this study was prospectively registered in PROSPERO (CRD42021244677). In total, 206 articles met our inclusion criteria, encompassing 372 ATs in 365 patients. Most ATs were apocrine‐eccrine ( n  = 217, 58.3%, n  = 173 benign) with a prevalence of poromas ( n  = 82), followed by follicular ATs ( n  = 88, 23.7%, n  = 83 benign) and sebaceous ATs ( n  = 67, 18.0%, n  = 49 benign). Most patients had a single AT lesion (320, 86.0%), while 42 (11.3%) had multiple ATs. A syndrome causing multiple ATs was identified in 15 patients. Histopathological analysis revealed 82% benign ( n  = 305) and 18.0% malignant ( n  = 67). ATs were classified according to their ability to mimic four groups of more common skin tumours: basal cell carcinoma, squamous cell carcinoma, melanocytic lesions and benign cutaneous lesions. Moreover, we have highlighted the ability of malignant variants of ATs to simulate benign skin lesions. This systematic review offers a comprehensive overview of the common clinical and dermoscopic features of follicular, sebaceous and apocrine‐eccrine ATs and details possible differential dermoscopic features.